Understanding The Concept And Application Of Islamic Education Evaluation Based On The Independent Curriculum In Junior High School - Habiba Waliulu; Woolnough Cale; Mahon Nitin; Snyder Bradford; Chandra Halim (Yayasan Adra Karima Hubbi, 2024)
Islamic education in junior high schools plays an important role in shaping students' character and morality. In this context, the concept of Islamic education evaluation based on the Merdeka Curriculum emerged as an effort to improve the quality of learning and ensure its relevance to the needs of the times. This study aims to understand the concept and application of Islamic education evaluation based on the Merdeka Curriculum in junior high schools. This is done to explore the effectiveness of this evaluation method in improving students' understanding of Islamic values and to see the extent of the implementation of the Merdeka Curriculum in the context of religious education. This research uses a qualitative approach with a case study. Data were collected through classroom observations, interviews with teachers and students, and document analysis related to the curriculum and evaluation of Islamic education in junior high schools. The results showed that the evaluation of Islamic education based on the Merdeka Curriculum can improve students' understanding of Islamic teachings and integrate them into their daily lives. Teachers report that this method allows them to be more flexible in adjusting learning to student needs as well as providing more targeted feedback. The conclusion of this study highlights the importance of using Merdeka Curriculum-based Islamic education evaluation in junior high schools as an effort to increase the relevance of learning to the context of students' lives. Effective implementation of this concept requires strong support from the school and teachers, as well as a commitment to continuously develop evaluation methods that are in line with Islamic values and the demands of the times